Measurement of fluid flow in closed conduits. Velocity area methods. Methods of flow measurement in swirling or asymmetric flow conditions in circular ducts by means of current-meters or Pitot static tubes Part 2.3, (31st May 1984) - British Standards Institution,
No abstract available